Corrigendum to “Determining patients’ willingness to pay for telemedicine services and associated factors amidst fear of coronavirus disease 2019 (COVID-19) in Ghana” [Volume 9, Issue 8, August 2023, e19191] - Godwin Adzakpah; Nathan Kumasenu Mensah; Richard Okyere Boadu; Jonathan Kissi; Michael Dogbe; Michael Wadere; Dela Senyah; Mavis Agyarkoaa; Lawrencia Mensah; Amanda Appiah-Acheampong (Heliyon)
Introduction: Understanding patients' Willingness to pay (WTP) for telemedicine and the factors that contribute to its implementation is important to help improve health policy planning. Despite the fact that information about patients' WTP for health services is crucial for planning, few studies have looked at it from the patient's perspective. This study therefore aims at examine patients' willingness to pay for telemedicine services and the factors that influence how much money are patients willing to pay for telemedicine services amidst the fear of coronavirus disease 2019 (COVID-19). Methods: We employed a cross-sectional survey design in soliciting responses from patients attending hospitals in six purposively selected health facilities in Ghana from October 2020 to November 2021. Mean, percentage, standard deviation, and frequency of appearance were used for the descriptive analysis. To test for normality and equal variance of the continuous variable, Shapiro-Wilk and Bartlett tests were used. The contingent valuation method was used to estimate the WTP for the telemedicine service, using an open-ended question format. Average WTP and factors associated with it were estimated using the Probit and Tobit models. Stata 15 was used to analyse the data and a p-value less than 0.05 was considered statistically significant. Results: In all, 1227 participants from six selected health facilities across the country were involved in the study. Male respondents were 44.3 % (543), while females accounted for 55.7 % (684). The proportion of people WTP for telemedicine services was 73.6 % (903). The stated average amount WTP for telemedicine services per visit was GHȻ55.55 (US$ 6.17) and the standard deviation was GHȻ52.61 with a 95 % confidence interval of GHȻ52.12 to GHȻ58.99. In the model estimation, mean WTP was GHC109.71 ($12.19). We found that age, gender, and fear of COVID-19 were statistically significantly associated to how much money are patients willing to pay for telemedicine services amidst the fear of COVID-19. Conclusion: Most of the patients were willing to use and pay for telemedicine services. Average willingness to pay ranges from GHC55.55 ($6.17) and GHC109.71 ($12.19). Age, gender, fear of catching covid-19, worried about managing health in the mist of covid-19 and delay in elective surgery were the variables associated with how much money patients were willing to pay for telemedicine services. There is therefore the need for healthcare providers to position themselves to provide remote care to patients in the safety and comfort of their homes.